Layered energy equalization structure for series battery pack based on multiple optimal matching - Jianfang Jiao; Hongwei Wang; Feng Gao; Serdar Coskun; Guang Wang; Jiale Xie; Fei Feng (Green Energy and Intelligent Transportation)
The equalization management system is an essential guarantee for the safe, stable, and efficient operation of the power battery pack, mainly composed of the topology of the equalization circuit and the corresponding control strategy. This article proposes a novel active balancing control strategy to address the issue of individual cell energy imbalance in battery packs. Firstly, to achieve energy equalization under complex conditions, a two-layer equalization circuit topology is designed, and the efficiency and loss of energy transfer in the equalization process are studied. Furthermore, a directed graph-based approach was proposed to represent the circuit topology equivalently as a multi-weighted network. Combined with a multi-weighted optimal matching algorithm, aims to determine the optimal energy transfer path and reduce equalization losses. In addition, a fuzzy controller that can dynamically adjust the equalization current with the state parameter of the cell as the input condition is designed to optimize the equalization efficiency. Matlab/Simulink software is used to build and simulate the model. The experimental results indicate that, under the same static state, the newly proposed control strategy improves efficiency by 6.08% and enhances equalization speed by 42.03% compared to the maximum value equalization method. The method also effectively improves energy utilization under the same charging and discharging states.